Serum biomarkers of maternal morbidity and adverse outcome in severe pre-eclampsia. (March 2022) - Keepanasseril, Anish; Bharathi, V.; Bobby, Zachariah; Kar, Sitanshu Sekhar; Parameswaran, Sreejith; Pillai, Ajith Ananthakrishna; Maurya, Dilip Kumar
Abstract: Objective: To evaluate the association of maternal serum biomarkers of myocardial damage, oxidative stress and angiogenic imbalance with maternal adverse outcomes in women with severe pre-eclampsia. Methods: This was a prospective cohort study, where maternal serum biomarkers were evaluated in women admitted with severe pre-eclampsia to a tertiary care centre between March 2019 and February 2020. Serum markers included brain naturetic peptide (BNP), cardiac troponin-T (cTnT), cystatin-C (cys-C), soluble fms-like tyrosine kinase-1 (sFlt-1), placental growth factor (PlGF), Total Anti-Oxidant status (TAO) and malondialdehyde (MAO). Main outcome measures were adverse maternal outcomes defined as eclampsia, pulmonary oedema, acute kidney injury, placental abruption and HELLP syndrome. Results: Adverse maternal outcomes occurred in 93(37.2%, 95% CI: 31.2%-43.6%) of the 250 women with severe pre-eclampsia included in the study, including 21 with pulmonary oedema, 25 with acute kidney injury and 36 with eclampsia. BNP levels were higher among women who developed pulmonary oedema (55.4 pg/mL vs 42.0 pg/mL, p = 0.008). TAO levels were higher in women who developed eclampsia (4.6 mM, IQR 3.1–5.7, p < 0.001) and acute kidney injury (4.1 mM, IQR 3.2–6.3, p = 0.002) compared to those who did not develop any complications (2.93 mM, IQR 2.3–4.1). Conclusions: Even though the endothelial dysfunction and oxidative stress biomarkers were associated with development of preeclampsia, it may have limited utility in identifying women who might develop adverse outcomes.